2017
DOI: 10.1002/pc.24383
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and morphological properties of cellulose nanocrystal‐polypropylene composites

Abstract: In this work, the rheological, mechanical, morphological, and thermal properties of cellulose nanocrystal (CNC)‐polypropylene (PP) composites prepared in the molten state were investigated. All samples contained a maleated PP used as combatibilizer. Degradation of the PP in the presence of CNCs at high processing temperature was shown to have a significant effect on the rheological behavior. For PPs with two different molecular weights and prepared at different temperatures, the tensile modulus of composites c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 50 publications
1
27
0
2
Order By: Relevance
“…Among nanoparticles generally, cellulose nanocrystal (CNC) is known for its superior mechanical properties, low cost, low density, abundance and renewability and is a promising candidate for generating new materials . In recent years, numerous studies have been undertaken to prepare CNC nanocomposites employing melt mixing, solvent casting, or a combination of both . For example, recently, Dhar et al demonstrated a single step reactive extrusion of PLA/CNC nanocomposites with improved processability, recyclability, and potential application for food packaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among nanoparticles generally, cellulose nanocrystal (CNC) is known for its superior mechanical properties, low cost, low density, abundance and renewability and is a promising candidate for generating new materials . In recent years, numerous studies have been undertaken to prepare CNC nanocomposites employing melt mixing, solvent casting, or a combination of both . For example, recently, Dhar et al demonstrated a single step reactive extrusion of PLA/CNC nanocomposites with improved processability, recyclability, and potential application for food packaging.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] In recent years, numerous studies have been undertaken to prepare CNC nanocomposites employing melt mixing, solvent casting, or a combination of both. 2,[23][24][25][26][27][28][29][30][31] For example, recently, Dhar et al 29,30 demonstrated a single step reactive extrusion of PLA/CNC nanocomposites with improved processability, recyclability, and potential application for food packaging. Only a very few studies, however, have been conducted so far on the incorporation of CNCs into heterophase polymerpolymer systems.…”
mentioning
confidence: 99%
“…No agglomeration of particles was noticed and no gaps between nanocellulose and polyvinyl alcohol matrix were found in polyvinyl alcohol nanocomposite films. Hence, the reinforcing efficiency of fillers was increased and thus, the mechanical properties of polyvinyl alcohol nanocomposite films were enhanced .…”
Section: Resultsmentioning
confidence: 99%
“…[11] Cellulose reinforced polypropylene (PP) composites have been the subject of several studies. [21,[28][29][30][31][32][33][34][35] Different approaches have been used to improve the mechanical properties of these composites, such as adding a coupling agent or different processing routes. Maleic anhydride grafted polypropylene (PP-g-MAH) has been widely used to improve the dispersion and enhance the adhesion between the cellulose filler and PP matrix.…”
Section: Introductionmentioning
confidence: 99%